Investigation of teeth engagement conditions of cylindrical involute gear on contact strength, wear and durability. Part 3. Changeable interaction conditions in non-correlated engagement - Чернець, М.В.; Чернець, Ю.М. (Problems of Tribology, 2015)
According to calculation method of tooth gears’ wear and durability it has been conducted an investigation of influ-ence of double - single - double - tooth engagement on maximal contact pressures, teeth wear and gear durability at change-able contact conditions in non-correlated helical gearing taking into account the teeth contours change at the result of their wear. It is suggested the techniques of estimation of teeth curvature radii change at the process of their wear. It has been es-tablished that wear has significant influence on maximal contact pressures change in input phase of double-tooth engage-ment. Maximal wear is reached at the entrance into single-tooth engagement (spur gear) or at the entrance into double-tooth engagement (helical gearing). At the result of maximal initial contact pressures decrease in the process of teeth wear, gear du-rability increases by 19 %. The obtained results are presented graphically what allows showing the regularities of influence of engagement conditions.